Islam Sebagai Amanah Ketuhanan dan Kemanusiaan - Aulia, Nurul; Albina, Meyniar (UNIVERSITAS SERAMBI MEKKAH, 2025)
Islam, as a divine and humanistic trust, is a profound concept that emphasizes humanity's responsibility to live according to God's teachings. From God's perspective, Islam emphasizes that all humans have a strong spiritual bond with their Creator, which requires them to carry out the Creator's commands with full awareness and sincerity. Islam, on the other hand, is a humanitarian mission that calls on its followers to respect each other, do good, and uphold social justice. Teachings such as honesty, compassion and solidarity form the basis of interaction between people, and Islam is not only spiritually important, but also a practical guide for building a harmonious and civilized society. Therefore, understanding Islam as a divine and humanistic mission is the key to balancing vertical relationships with God and horizontal relationships with fellow humans.